Recovery from delirium and psychotic manifestations following treatment of anaemia with off-label rituximab in active cold haemagglutinin disease. (2nd February 2016) - Kaklamanos, Michail; Regmi, Sadie; Wrench, David; Kinirons, Mark
Abstract : Anaemia is an independent, commonly under-recognised risk factor for delirium. Prompt management of anaemia and its underlying aetiology could result in recovery from delirium and associated psychotic manifestations. We report this unprecedented case of complete recovery from delirium and challenging behaviour, following treatment of autoimmune haemolytic anaemia with rituximab.